PENTAMETHYLCARBOXYLATE RUTHENOCENE BASED ANTITUMOUR AGENT - Wahjuni, Sri; Puspawati, Ni Made; Williams, Michel (BALI MEDICAL JOURNAL; Vol 4 No 2 (2015), 2015)
Background: Unlike iron ruthenium is not an essential element for life. However, the behavior of ruthenium compounds in biological systems and, in particular their use as antitumour agents has attracted much attention recently. This study aims to determine antitumour properties against human tumour cell line HeLa of pentamethylcarboxylate ruthenocene. Methods: This is an in vitro study by applying an experimental within post only control group design. Cisplatin, a clinical used medicine was applied for control. The human tumour cell line Hela was used for the test. The cells were cultured at 370C in 5% CO2/air in Roswell Park Memorial Institute Medium 1640 and seeded overnight in 96 well microtitre plates. The penthamethylcarboxylate ruthenocene was dissolved in 1,2 dimethoxy ethane and diluted with culture media. The plates were assays by measuring optical density in the range of 490-655 nm. The D37 values were then calculated. Results: The pentamethylcarboxylate ruthenocene compound tested was found to be more cytotoxic than cisplatin (with D37 = 422 nM compare to D37 = 705 nM for cisplatin). Conclusions: The compound tested, pentamethylcarboxylate ruthenocene was found more potent as an antitumor compare to cisplatin a clinical used antitumor for curing testicular carcinoma.
Keywords: iron, essential, element, cell, potent